ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI PADA USAHATANI JAGUNG HIBRIDA DI KECAMATAN TIBAWA KABUPATEN GORONTALO - Indahsari Kilo; Amir Halid; Asda Rauf (Universitas Negeri Gorontalo, 2018)
This research aims to analyze: 1) performance of hybrid corn farming business in Sub-district of Tibawa, District of Gorontalo; 2) level of profit and hybrid corn farming business suitability in Sub-district of Tibawa; and 3) factors of production that affect production of hybrid corn Sub-district of Tibawa, District of Gorontalo. This research is conducted in Sub-district of Tibawa, District of Gorontalo, from August to September 2017 by having 50 farmers as samples. Thias research applies and Cobb-Douglass production function analysis. Research finding reveals that performance of corn farming business has not yet implemented cultivation technique that is based on theory and advices of the extension man. Monoculture performance of hybrid corn farming business consists of land processing, planting, weeding, fertilizing, maintaining and harvesting. The applied farming business system is just based on personal experience of every farmer and it is not performed intensively. Utilization of production facility is not based on agricultural advices. TKLK (Workers out of Family Member) is more often used than TKDK ( Workers from Family Member). Finding of analysis using R/C also reveal that hybrid corn farming business in Sub-district of Tibawa makes profit for IDR. 6.826.827,48. Value of R/C at hybrid corn farming business is 1,64, then based on criterion of R/C ratio is 1, thus the farming business in Sub-district of Tibawa is proper to be developed. Utilization of production factors at hybrid corn farming business simultaneously and positively as well as significantly influences production of the hybrid corn, while partially, seed and fertilizer positively and significantly influences the production.